Temporomandibular joint dislocation in an 18-month-old child - Jaeson Mohanan Painatt; Ravi Veeraraghavan; Ushass Puthalath (Wolters Kluwer Medknow Publications, 2017)
Temporomandibular joint (TMJ) dislocation in children is extremely rare. In our case, an 18-month-old child presented with a history of inability to close her mouth. To confirm the clinical diagnosis, a computed tomogram was taken. Clinical examination and X-ray of the TMJ revealed bilateral TMJ dislocation. Bilateral TMJ reduction was achieved manually after giving analgesia and procedural sedation. This is one of the few case reports of an acute dislocation in a toddler.